PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN NUSANTARA KE BALI ZOO PADA ERA NEW NORMAL - Angita Dita Sari; Ni Made Sofia Wijaya; I Made Kusuma Negara (Jurnal IPTA (Industri Perjalanan Wisata), 2022)
Electronic Word Of Mouth (EWOM) is a positive or negative statement that is formed from the opinions of consumers, both prospective and former consumers of a product that can be accessed by a wide audience in cyberspace. The number of tourists visiting Bali Zoo cannot be separated from promotions carried out through social media which makes it easy to convey information about their products or services in various forms such as text, images and videos. This study aims to determine the effect of Intensity, Content, Valence of Opinion on the Decision of Domestic Tourists to Visit Bali Zoo in the new normal era. The research method used ordinal regression analysis. The sampling technique was taken by purposive sampling and data were collected 100 respondents of domestic tourists who had visited the Bali Zoo in the new normal era. Data collection techniques used in this study by means of observation, documentation, questionnaires and literature study. Ordinal regression results on parameter estimates for test results on electronic word of mouth variables with indicators X1.1, X2.2, X3.1 and X3.3 obtained sig. 0.044 (0.05), 0.006 (0.05), 0.023 (0.05), and 0.000 (0.05) with an estimated value for X1.1 of 4.047, X2.2 of 7540, X3.1 of 5206, and X3.3 of 12,643. H4a is accepted and H4o is rejected. It is examined that EWOM affect the decision of tourist to visit Bali Zoo in the new normal era.